Preface - Editorial Team , EICCS (Evolution of Information, Communication and Computing System, 2022)
Through numerous technological advances, society is moving towards the Internet of Things (IoT) paradigm. People start to stay connected with their things either to monitor or to view the conditions of their things. IoT is a mixture of wireless sensor network (WSN) technology, communication technology, sensor technology, and Internet technology. The ability to connect, communicate with, and remotely manage an incalculable number of networked, automated devices via the Internet become pervasive, from the agricultural farming to commercial kitchen to the residential basement room to the arm of the fitness buff.